A prospective cohort study of self-reported computerised medical history taking for acute chest pain: protocol of the CLEOS-Chest Pain Danderyd Study (CLEOS-CPDS) - Carl Johan Sundberg; Thomas Kahan; Jonas Spaak; Helge Brandberg; Kay Sundberg; Sabine Koch; Athena Adeli; David Zakim (BMJ Open)
Introduction Management of acute chest pain focuses on diagnosis or safe rule-out of an acute coronary syndrome (ACS). We aim to determine the additional value of self-reported computerised history taking (CHT).Methods and analysis Prospective cohort study design with self-reported, medical histories collected by a CHT programme (Clinical Expert Operating System, CLEOS) using a tablet. Women and men presenting with acute chest pain to the emergency department at Danderyd University Hospital (Stockholm, Sweden) are eligible. CHT will be compared with standard history taking for completeness of data required to calculate ACS risk scores such as History, ECG, Age, Risk factors and Troponin (HEART), Global Registry of Acute Coronary Events (GRACE), and Thrombolysis in Myocardial Infarction (TIMI). Clinical outcomes will be extracted from hospital electronic health records and national registries. The CLEOS-Chest Pain Danderyd Study project includes (1) a feasibility study of CHT, (2) a validation study of CHT as compared with standard history taking, (3) a paired diagnostic accuracy study using data from CHT and established risk scores, (4) a clinical utility study to evaluate the impact of CHT on the management of chest pain and the use of resources, and (5) data mining, aiming to generate an improved risk score for ACS. Primary outcomes will be analysed after 1000 patients, but to allow for subgroup analysis, the study intends to recruit 2000 or more patients. This ongoing project may lead to new and more effective ways for collecting thorough, accurate medical histories with important implications for clinical practice.Ethics and dissemination This study has been reviewed and approved by the Stockholm Regional Ethical Committee (now Swedish Ethical Review Authority). Results will be published, regardless of the outcome, in peer-reviewed international scientific journals.Trial registration number This study is registered at https://www.clinicaltrials.gov (unique identifier: NCT03439449).